Effect of metal catalysts type and annealing time on the growth of zinc oxide nanostructures by thermal vapor deposition method - Rosli, Anis Diyana Hashemi; Yusof, Khairul Aimi; Herman, Sukreen Hana; Johari, M. H.; Shariffudin, Shafinaz Sobihana; Ani, Mohd Hanafi (Trans Tech Publications, Switzerland, 2014)
This paper reports the results of zinc oxide (ZnO) nanostructure growth on different types of metal catalysts, namely gold and platinum, and also the effect of annealing time of the metal catalysts prior to the deposition of ZnO nanostructures. The metal catalysts layers with 15 nm thickness were deposited on glass substrates by sputter coater and then annealed in air ambient for 15 and 30 min at 500 ˚C. ZnO nanostructure was then deposited on the metal catalysts by thermal chemical vapour deposition (TCVD) method. We found that the Au catalyst morphologies varied with the annealing time, and the growth morphology of the ZnO followed the morphology of the Au catalyst. The morphology of the metal catalysts and ZnO nanostructures were characterized using field emission scanning electron microscopy (FESEM). The grown ZnO nanostructures were tested for their ability for extended gate field effect transistor (EGFET) sensor application. The samples were attached to the gate of an NFET and were dipped in acid and alkali buffer solutions while the gate voltage was measured. We found that the extended gate gave different voltage in buffer solutions with different pH which indicated that the samples can act as the extended gate of an EGFET sensor.